How are early maladaptive schemas and DSM‐5 personality traits associated with the severity of binge eating?. Issue 3 (16th November 2019) - Aloi, Matteo; Rania, Marianna; Caroleo, Mariarita; Carbone, Elvira A.; Fazia, Gilda; Calabrò, Giusy; Segura‐Garcia, Cristina
Abstract: Objective: The present study aimed to (a) assess and compare personological traits and early maladaptive schemas (EMSs) of obese women with and without binge eating disorder (BED) and (b) identify the variables associated with the binge severity. Method: One hundred women (55 BED‐obese and 45 non‐BED‐obese) completed psychopathological and personological self‐report questionnaires. A forward stepwise linear regression analysis was performed to assess variables associated with binge eating severity. Results: Not only psychopathological but also personological differences were evident between BED and non‐BED‐obese women. BED severity was significantly associated with depressivity, emotional deprivation, and defectiveness. Conclusions: Our preliminary findings suggest that BED patients exhibit some EMSs that could be linked to the construct of emotional neglect and specific personological traits closely related to depressive dimensions, emotional lability, and impulsivity. In particular, binge severity is associated with the pervasiveness of depressogenic cognitive schemas, as well as those of emotional deprivation and defectiveness.